A ATUAÇÃO DO ESTADO, VIOLÊNCIA E PRÁTICAS JURÍDICAS CONTRA CRIANÇAS E ADOLESCENTES UMA ANÁLISE A PARTIR DA PSICOLOGIA SOCIAL (Reflection and Critique Law Magazine, 2026)
The study analyzes state violence against children and adolescents in Brazil, highlighting its structural and institutional dimensions. Despite the advanced legal framework, such as the Statute of the Child and Adolescent (ECA), systematic violations persist, especially against vulnerable groups. The study addresses four main areas: violence in the judicial sphere, marked by racial and socioeconomic selectivity; the socio-educational system, which often reproduces violence instead of resocializing; schools as ambiguous spaces, which can both protect and reproduce violence; and social psychology as a transformative tool, proposing multidisciplinary interventions and integrated public policies. The research highlights the need to break with fragmented approaches and invest in actions that combine welcoming, qualified listening, and profound institutional changes.Keywords: ECA; state violence; children and adolescents; socio-educational system.